Sovremennye instrumental'nye i komp'juternye technologii ocenki skorostno-silovych sposobnostej sportsmena - Samborskij, A. G.; Samborskij, A. A. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The efficient control of a course of training process of athletes demands a regular estimation of their main physical qualities. In the basic kinds of sports such conducting physical qualities are force, speed and their joint display - capacity. Precisely estimating the time characteristics of display of the specified qualities, it is possible to bring in rather valuable corrective amendments to the process of training of athletes.